Germination seed response of Eleusine indica L. Gaertn to depth and buried time - Astria Sari Munthe; Edison Purba Purba; Ratna Rosanti Lahay (Jurnal Agroekoteknologi, 2016)
A population of Eleusine indica L. Gaertn multiple resistant biotype securred in an oil palm field in North Sumatra. Field experiment was carried out to determinate the effect of time of period and depth seed buried in the soil on germination, effect of seed position buried in the soil on their emergence and number of seed bank found in various depth of soil. The study was conducted at Agricultural Faculty, University of Sumatera Utara. This research used randomized block design with 3 unit and 4 replication, first unit was germination response of seed weed E. indica to dept buried time with 2 factors. The first factor was dept with 5 treatment i.e. 0, 5, 10, 15, and 20 cm. The second was buried time with 6 treatments i.e. 2, 4, 6, 8, 10, and 12 weeks. Second unit was germination seed response of E. indica to various depth with 5 treatment i.e. 0, 5, 10, 15, and 20 cm. Third unit was seed bank E. indica with 4 treatment i.e. 0-5, 5-10, 10-15 and 15-20 cm.   The results showed that the buried depth does not treatment affect the germination, but on buried time treatment affects on the germination. Seed germination buried for 12 weeks, number of seeds germination is higher than along 2, 4, 6, 8, 10 weeks. The depth of buried seeds (planting) effect on number of sprouts that appear on the surface of the soil. The highest number appears there are at 0 cm below the soil surface followed by 5 cm. The highest number of seed bank in the field are at a depth of 0-5 cm soil followed by a 10-15, 5-10, 15-20 cm. Keywords : Eleusine indica, buried time, depth